Value addition of tilapia (Oreochromis niloticus): Preparation of fillet and shelf-life assessment (Research in Agriculture Livestock and Fisheries, 2021)
Although tilapia is one of the most cultivated fish species in Bangladesh owing to its high growth rate, comparatively easy culture practices, higher survival rate and short culture period but low market preference marked it as a low-priced fish. Various approaches have been adopted to enhance consumer acceptability and ensure better use of tilapia, including the production of value-added products such as tilapia-prepared fillets, which attract increasing interest. Therefore, the current study was designed and carried out in order to prepare tilapia fillets and to estimate their shelf life at frozen (-18±20C) and refrigerated (4±10C) temperatures. Fillets were produced from tilapia collected from local fish markets of Sylhet city, Bangladesh with according to Good Manufacturing Practices (GMP) established by International Standards Organization (ISO) and packed in polyethylene bags. Proximate composition, total volatile base nitrogen (TVBN), peroxide value (PV), pH, total plate count (TPC) and sensory properties of fillets were analyzed to determine shelf-life. A portion of the fresh fillet sample was immediately analyzed and the remaining portions were preserved for up to 12 and 90 days at refrigerated and frozen storage temperatures, respectively. Results revealed that, at a definite interval of time, changes in the chemical, microbial and sensory attributes of tilapia fillets were found to be more pronounced in refrigerated storage conditions than fillets stored in frozen conditions. The shelf life of refrigerated and frozen tilapia fillet samples was 9 and at least 90 days, respectively, per the results of sensory, microbial and chemical evaluation.Res. Agric., Livest. Fish.8(2): 231-240, August 2021